Channel Impulse Response Estimation in IEEE 802.11p via Data Fusion and MMSE Estimator. (30th March 2015) - Ministeri, Giulio; Vangelista, Lorenzo
Abstract : Tracking the channel impulse response in systems based on the IEEE 802.11p standard, the most widely accepted standard for the physical layer in vehicular area networks (VANETs), is still an open research topic. In this paper we aim to improve previously proposed channel estimators by utilizing data aided algorithm that includes the channel decoding to enhance the quality of the estimated data. Moreover we propose a novel technique that exploits information provided by external sensors like GPS or speedometer, usually present in vehicles. The algorithm proposed so far has been analyzed in non-line-of-sight link conditions; in this paper we present an analysis of performances in the line-of-sight condition as well. Simulations show that both proposals give considerable improvements in terms of packet error rate and channel estimation error in the highway scenario which is surely the most stressing environment for the channel response tracker.